Stunting Perception among Stakeholders: A Qualitative Study - Patimah, Sitti; Khalid, Sajidah Hardiyanti; Asrina, Andi; Septiyanti, Septiyanti (Media Gizi Indonesia, 2024)
Majene Regency had the highest prevalence of stunting in West Sulawesi province in 2018. Addressing this issue requires an integrated approach involving various stakeholders. Understanding their perceptions of stunting is crucial. This study aimed to analyze stakeholders' perceptions of stunting using a Quasi-Qualitative method with a descriptive approach. Data were collected through in-depth interviews, focus group discussions, and observations. Stakeholders responsible for specific and sensitive nutrition interventions in Majene District were selected via purposive sampling. These included the Health Office, Education Office, Women's Empowerment and Child Protection Office, Ministry of Religion, Regional Development Planning Agency, and nutrition officers at the Sendana I Public Health Center. The results revealed differing perceptions among stakeholders about the causes, impacts, prevention, and control of stunting. They viewed stunting as a failure to thrive due to chronic malnutrition, with impacts such as growth disorders, low cognitive abilities, and reduced competitiveness. Each stakeholder had a unique perspective on stunting prevention and management based on their job duties. The study concluded that differing perceptions among stakeholders regarding stunting's causes, impacts, and management stemmed from their varied knowledge and responsibilities. Achieving a common understanding among stakeholders is essential to effectively control stunting through a convergent approach.